Simulation of the Effect of Small‐Scale Mountains on Weather Conditions During the May 2021 Ultramarathon in Gansu Province, China. Issue 15 (9th August 2022) - Xue, Haile; Li, Jian; Zhang, Qinghong; Gu, Hongping
Abstract: Hypothermia killed 21 participants of the 100 km cross‐country Ultramarathon Mountain race in Baiyin, Gansu Province in northwestern China on 22 May 2021, when a large‐scale cold front passed by the race site. The hypothermia was caused by low temperatures, high winds, and hail‐like precipitation, as reported by survivors. However, there is no meteorological station near the race site, leading to a lack of data on the exact weather conditions during the race. Considering the complex topography of the race site, the weather conditions must be re‐built using high‐resolution model simulations, so that the tragedy can be investigated. In this study, the weather conditions in this mountainous area were simulated using the Weather Research and Forecasting model with a 333 m horizontal grid size. The results show that interaction between the mountain wind and orographic precipitation led to a 6.7°C decrease in temperature and a 12 m s −1 increase in wind speed. Precipitation increased owing to orographic accent and convergence, and fell as graupel. High‐speed downslope winds were the result of large‐amplitude trapped lee waves. The combination of low temperatures, high winds, and spillover graupel on the lee resulted in the blizzard‐like weather during the race, thus the hypothermia amongst the runners. The apparent temperature was estimated to be as low as −10°C. Our study shows that mesoscale numerical models with a grid size of hundreds of meters should be used to improve weather forecasts in mountainous regions and prevent future tragedies for special events. Key Points: A small‐scale mountain played a key role in the weather conditions that caused 21 deaths of hypothermia during an ultramarathon The spillover graupel and high downslope winds led to blizzard‐like weather on the lee and an apparent temperature of −10°C Mesoscale numerical models of hundreds‐meter resolution may improve weather forecasts in mountainous regions to prevent future tragedies